PENGARUH LATIHAN UPHILL TERHADAP KECEPATAN LARI ATLET FUTSAL KLUB DEDAK FC - Aswandi Aliang; Mimi Haetami; Noviyanti Noviyanti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstrakThis study aims to increase the running speed of athletes or futsal players, namely increasing running speed with Uphill training at the futsal club of Dedak Fc athletes. This research was conducted using quantitative descriptive analysis with experimental research methods as many as 12 meetings. and this research design uses a one-group pre-test-post-test design and uses a research instrument in the form of a 30-meter sprint test. The subjects of this study were all athletes of the futsal club Dedak Fc which operated 10 people located in North Pontianak, Pontianak city. Based on the results of the study, it can be said that there is an effect of Uphill exercise on the running speed of Dedak Fc futsal athletes with an increase in the percentage of individuals, then the good category group remains in the good category experiencing an insignificant increase of 16.13%, and the good category 16, 41%, then from the good category, there was an increase to the very good category by 29.45%, if it was calculated as a whole, the average percentage of athletes increased by 27.65%. The effect size of the effect of uphill training on the running speed of the futsal club Dedak Fc athletes is 0.206 (small effect). Thus, the researcher hopes that this study can increase the running speed of a reference for athletes' running improvement programs.Keywords: Futsal, Running uphill